A woman of adventure the life and times of First Lady Lou Henry Hoover - Dunlap, Annette, 1955- (Potomac Books, an imprint of the University of Nebraska Press, 2022)
Annette B. Dunlap takes a fresh look at Lou Henry Hoover, the First Lady who preceded Eleanor Roosevelt, from Hoover's relief efforts during World War I to her work developing organizations that promoted self-sufficiency among young girls and women.